2017
DOI: 10.1007/s12306-017-0483-y
|View full text |Cite
|
Sign up to set email alerts
|

Immediate intensive mobilization compared with immediate conventional mobilization for the impacted osteoporotic conservatively treated proximal humeral fracture: a randomized controlled trial

Abstract: Level 1, randomized controlled double-blinded trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“… 8 The goal after surgical fixation is to allow early range of motion, an important postoperative factor that maximizes the potential for a good clinical outcome. 9 - 11 Although many of these fractures may be managed nonoperatively, particularly in the elderly, instances where surgical treatment will yield an improved clinical outcome if complications are avoided. 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“… 8 The goal after surgical fixation is to allow early range of motion, an important postoperative factor that maximizes the potential for a good clinical outcome. 9 - 11 Although many of these fractures may be managed nonoperatively, particularly in the elderly, instances where surgical treatment will yield an improved clinical outcome if complications are avoided. 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…The population enrolled displayed clinical and sociodemographic characteristics similar to patients with PHFs and undergoing conservative or surgical treatment in Italy and the United Kingdom [25,26]. However, outcome measures slightly differed in the above studies and, therefore, a full comparison cannot be stated, therefore this fact partially limits the generalizability of our results.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly to the CSR on elbow fractures, just small single trials have been found with serious imprecisions that suggest caution in interpreting the results [ 22 ]. The incidence of proximal humerus fractures is growing among elderly osteoporotic patients [ 34 ] where, due to lower functional needs, surgery is often avoided [ 35 ]. The common practice of non-surgical approaches in proximal humeral fractures (up to 80% of these fractures) includes the use of sling immobilization [ 36 ].…”
Section: Discussionmentioning
confidence: 99%